Skrining Fitokimia Ekstrak Metanol Dari Daun Jati Belanda (Guazuma ulmifolia) - Yuliandari, Fadhira; Parbuntari, Hesty (Departemen Kimia FMIPA UNP, 2023)
Dutch teak (Guazuma ulmifolia) is a plant that belongs to the family Sterculiaceae and grows in Ecuador, Panamaa, and other American Latin countries. This Dutch teak is found in bushes, as well as in forests. This Dutch teak plant is often the most needed for health, especially the leaves. Dutch teak leaves have been used as traditional medicine to maintain a healthy body, lose weight as a slimming herb, to lowers cholesterol levels in the body. Research has been done phytochemical screening to determine the secondary metabolites contained in Guazuma ulmifolia. Phytochemicals test results showed that Guazuma ulmifolia contains secondary metabolites in the form of flavonoids, steroids, alkaloid, and saponins.